2005
DOI: 10.1590/s0034-70942005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da dexmedetomidina sobre o sistema renal e sobre a concentração plasmática do hormônio antidiurético: estudo experimental em cães

Abstract: In anesthetized dogs, low doses of dexmedetomidine inhibit vasopressin secretion, causing aqueous diuresis. These actions might protect kidneys during ischemic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 19 publications
0
17
0
2
Order By: Relevance
“…Studies performed on canines undergoing general anesthesia have shown that dexmedetomidine has a diuretic-like effect associated with a decreased urine osmolarity, increased free water clearance, and a reduction in plasma vasopressin levels. These studies suggest that dexmedetomidine may induce both vasopressin suppression and responsiveness [4-5]. In humans, it is currently unknown if dexmedetomidine causes an inadequate secretion of vasopressin (a central mechanism) or if it decreases the responsiveness of the renal tubules to vasopressin (a peripheral cause).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed on canines undergoing general anesthesia have shown that dexmedetomidine has a diuretic-like effect associated with a decreased urine osmolarity, increased free water clearance, and a reduction in plasma vasopressin levels. These studies suggest that dexmedetomidine may induce both vasopressin suppression and responsiveness [4-5]. In humans, it is currently unknown if dexmedetomidine causes an inadequate secretion of vasopressin (a central mechanism) or if it decreases the responsiveness of the renal tubules to vasopressin (a peripheral cause).…”
Section: Discussionmentioning
confidence: 99%
“…In animal models propofol reduced markers of oxidative stress in the kidney [165, 166] and dexmedetomidine caused diuresis through reducing vasopressin secretion, enhancing renal blood flow and hence glomerular filtration [167] and showed renal protection [168171]. …”
Section: Sedationmentioning
confidence: 99%
“…The α 2 -adrenoreceptors are widely distributed in the renal proximal and distal tubules, peritubular vasculature as well as in systemic tissues [15]. Dexmedetomidine treatment has been found to inhibit vasopressin secretion, enhance renal blood flow and glomerular filtration, and increase urine output [16-18]. Dexmedetomidine also has a cytoprotective effect against renal I/R injury.…”
Section: Introductionmentioning
confidence: 99%